Disclosure of financial ratios in the annual reports / Mariam Rahmat - Rahmat, Mariam (Universiti Teknologi MARA, Sarawak, 2001)
The usefulness of financial ratios has been recognized by many researchers. It has increasingly become an important area of accounting research and practice as it can be used for all kind of purposes. Even though the utilities of financial ratios have received much attention in the literature, until now, there has been no mandatory requirement to publicly disclose financial ratios except for earnings per share. However, evidence shows that many companies within Australia and elsewhere elect to voluntarily disclose financial ratios in their annual reports. This paper investigates financial ratio voluntarily disclosed in the annual reports of the top 60 public companies listed in the Australian Stock Exchange for 1996. Findings indicate that many ratios were disclosed in the financial summaries and financial highlights while dividend per share was the most popular ratios being disclosed. The findings also indicate that many different formulae were used in calculating those ratios.